Missing Lyrics in English Songs: Improving Listening Skills in SMP 16 Palu - Megasari Mongi; Hastini Hastini; Moh Abraham Akbar Eisenring; Wahyudin Wahyudin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research investigates the effectiveness of using missing lyrics in English songs to improving listening skills of the ninth-grade students at SMP 16 Palu. The research applied a quasi-experimental approach involving two groups: an experimental group that experiences the treatment using missing lyrics in English songs, and a control group that continued with the traditional learning skills before and after intervention. The results revealed that the experimental group showed a notable improvement in their listening skills compared to the control group. Using missing lyrics in English songs helped improve students’ interest and active participation during lessons. Additionally, this method provided genuine exposure to the English language. Overall, the findings indicate that incorporating missing lyrics in English songs can be an effective technique to support and develop students listening skills in language learning.